Resveratrol Brain Delivery for Neurological Disorders Prevention and Treatment - Andrade, Stephanie; Ramalho, Maria João; Pereira, Maria do Carmo; Loureiro, Joana A. (Frontiers in Pharmacology, 2018)
Resveratrol (RES) is a natural polyphenolic non-flavonoid compound present in grapes, mulberries, peanuts, rhubarb and in several other plants. Numerous health effects have been related with its intake, such as anti-carcinogenic, anti-inflammatory and brain protective effects. The neuroprotective effects of RES in neurological diseases, such as Alzheimer’s (AD) and Parkinson’s (PD) diseases, are related to the protection of neurons against oxidative damage and toxicity, and to the prevention of apoptotic neuronal death. In brain cancer, RES induces cell apoptotic death and inhibits angiogenesis and tumour invasion. Despite its great potential as therapeutic agent for the treatment of several diseases, RES exhibits some limitations. It has poor water solubility and it is chemically instable, being degraded by isomerization once exposed to high temperatures, pH changes, UV light or certain types of enzymes. Thus, RES has low bioavailability, limiting its biological and pharmacological benefits. To overcome these limitations, RES can be delivered by nanocarriers. This field of nanomedicine studies how the drug administration, pharmacokinetics and pharmacodynamics are affected by the use of nanosized materials. The role of nanotechnology, in the prevention and treatment of neurological diseases, arises from the necessity to mask the physicochemical properties of therapeutic drugs to prolong the half-life and to be able to cross the blood-brain barrier (BBB). This can be achieved by encapsulating the drug in a nanoparticle (NP), which can be made of different kinds of materials. An increasing trend to encapsulate and direct RES to the brain has been observed. RES has been encapsulated in many different types of nanosystems, as liposomes, lipid and polymeric NPs. Furthermore, some of these nanocarriers have been modified with targeting molecules able to recognize the brain areas. Then, this article aims to overview the RES benefits and limitations in the treatment of neurological diseases, as the different nanotechnology strategies to overcome these limitations.